14. Congreso Latinoamericano de Avicultura. Avicultura del sur del mundo : Memorias. Santiago de Chile, Chile 10 al 13 de Oct, 1995 - Albers, G.A.A.; Arias, J.L.; Fernandez, M.S.; Dale, N.; Gago Fernandez, A.; Nys, I.; Korver, D.; Klasing, K.; Leeson, S.; Mateos, G.G.; Piquer, J.; Garcia, M.; et al. (Santiago de Chile (Chile), 1995)
Sumario (Es, En)
Ilus.
Keywords: AVICULTURA; AVES DE CORRAL; ANIMALES DOMESTICOS; PRODUCCION ANIMAL; MEJORAMIENTO ANIMAL; RAZAS (ANIMALES); ADN; GENES; VARIACION GENETICA; CASCARA DE HUEVO; HUEVOS; NUTRICION ANIMAL; METODOS; CONTROL DE CALIDAD; LABORATORIOS; COMPOSICION APROXIMADA; MINERALES; PROTEINAS; PATOLOGIA; INMUNOLOGIA; NECESIDADES DE NUTRIENTES; NUTRICION ANIMAL; POLLO; SUBPRODUCTOS; VALOR NUTRITIVO; GRASAS; EVALUACION; INCUBACION DE HUEVOS; MORTALIDAD; REPRODUCCION; AVESTRUZ; INDUSTRIA; ENFERMEDADES INFECCIOSAS; POLLO DE ENGORDE; VIROSIS; FUNCION FISIOLOGICA; HEPATITIS; DIAGNOSTICO; CIENCIA ANIMAL; ZOOTECNIA; VACUNACION; DISTRIBUCION GEOGRAFICA; AMERICA LATINA; MEMORIA; CONGRESO